Insights from the transcriptome and metabolome into the molecular basis of diapause in Leguminivora glycinivorella (Lepidoptera, Olethreutidae) - Bingshuo Shi; Bei Chen; Zhentao Ren; Haimeng Zhao; Laipan Liu; Biao Liu; Kun Xue (PLoS ONE, 2025)
Leguminivora glycinivorella is a major pest in soybean production, causing huge economic losses to soybean production when the damage is severe, It typically usually overwintering with mature larvae lagging, which may be an effective tool for pest management. In this study, the key substances of diapause regulation were identified by differential expression genes and differential metabolites, using transcriptome and metabolomics analyses in the diapause and pre-diapause stages in L. glycinivorella. The findings revealed that 5558 genes in total were significantly altered during diapause, with pyruvate kinase (PK), trehalose synthase (TPS), superoxide dismutase (SOD), citrate synthase (CS), and 20-hydroxyecdysone (20E) showing significant decreases. There were 1628 metabolites with significant changes, especially proline, Phosphatidyl choline, and unsaturated fatty acids increased significantly in the period of diapause. Meanwhile, KEGG analysis based on the above differential substances showed that they were involved in TCA cycle, glycolysis, and glycerophospholipid metabolic pathway, which suggesting that they may be closely related to energy reserve, antioxidant regulation and hormone regulation during diapause. In this study, we present a comprehensive transcriptomic and metabolomic analysis that identifies three important molecular events during diapause (energy reserve, immune enhancement, hormone regulation) that may play a role in survival and stress resistance during diapause. These findings have greatly improved our understanding of diapause of L. glycinivorella, provided a theoretical basis for clarifying the molecular mechanism of diapause regulation of L. glycinivorella, and further improved the level of prediction and comprehensive management of L. glycinivorella.